Proceedings of the 9th International Conference on Civil Engineering - Feng, Guangliang (Lecture Notes in Civil Engineering,, 2023)
This open access book is a compilation of selected papers from the 9th International Conference on Civil Engineering (ICCE2022). The work focuses on novel research findings on seismic technology of civil engineering structures, High-tech construction materials, digitalization of civil engineering, urban underground space development. The contents make valuable contributions to academic researchers and engineers.